O ensino de futebóis na Educação Física escolar: dilemas, desafios e possibilidades - Murilo Otávio Menezes Costa (2024)
The main objective of this study is to investigate the teaching of football in school Physical Education (PE) and the didactic implications that involve the process of teaching this cultural content. The general objective of this research was to develop and investigate a proposal for football classes, seeking to reflect on the teaching and learning experienced in the process of its implementation. This general objective is divided into the following specific objectives: To analyze the teaching of football in school Physical Education and its possibilities; to understand the presence of football in school and in Physical Education classes; to produce a proposal for classes on the Teaching of Football in PE classes; to verify the forms of interaction of students with the proposals of “Futebóis”. This study is qualitative in nature and makes use of the theoretical-methodological premises of teaching-research. The research mobilized concepts arising from sociological and anthropological studies on football (Daolio, 1989; Scaglia, 1999, 2003; Faria, 2014; Silva; Cordeiro; Campos, 2016), on the teaching of football at school (Silveira; Pinto, 2008; Souza Junior; Darido, 2010; Faria; Santana, 2020) and on school PE (Bracht, 1997; Vago, 2009; Machado et al., 2010; González, 2019). The investigation showed that it is possible to expand and qualify students' relationship with the theme of football, either through access to conceptual knowledge or through bodily experimentation of other ways of playing football. The theme of “Football” proposed by Rezer (2009) proved to be powerful for thinking about and carrying out experiments to diversify the relationship between the research teacher and students with the theme of football, producing other possibilities for reading and producing meanings about this theme of body culture, forms that expand the meanings expressed in social media, television culture and diverse cultural practices. The study also shows that students’ resistance to the treatment of the theme of “Football” in school can be minimized or addressed through greater student participation in the process of proposing, designing, organizing and evaluating didactic proposals that aim to overcome the false understanding that school and PE have nothing to teach about football, since the learning experiences lived in cultural practices would make this learning possible. Finally, we point out the need for new studies on the subject, studies that take into account other contexts of schooling and other methodological approaches to the subject of football in order to broaden the reflection on the processes of schooling football in PE at school.